Unlocking the Potential of Facebook as a Versatile Platform for Knowledge Sharing - Enwereji, Prince; van Rooyen, Annelien Adriana; Morgan, Ilse (Research in Social Sciences and Technology, 2024)
Social network sites, most notably Facebook, have fundamentally transformed the way information is transferred, received, and shared by individuals and organisations. This article explores the diverse contexts in which Facebook is utilised as a knowledge-sharing instrument, along with the key challenges encountered in adopting Facebook as a knowledge-sharing instrument. It also indicates the gaps in adopting Facebook as a knowledge-sharing instrument. In a systematic literature review, 400 articles accomplishing the research objectives were identified. The findings revealed that Facebook can be used in different contexts. Greater awareness of Facebook’s versatility as a platform for knowledge sharing across various domains is recommended. This article also advises that the challenges related to cost, time investment and technical expertise be addressed, and emphasises the need for education and training.